Productive performance of growing guinea pigs (Cavia porcellus) subjected to different levels of dietary selenium - Aliaga Rota, Ada del Pilar (2020)
The study aimed to determine the effect of three levels of selenium on the diet of growing guinea pigs. Thirty-three weaned guinea pigs, 12 days old and with an body weight of 258 ± 35 g were randomly distributed in three treatments whose only difference was the content of selenium in the feed: 0.10, 0.17 and 0.24 mg Se/kg of feed for T1, T2 and T3, respectively. The animals received a ration without forage supply, with vitamin C supplementation and were housed in individual cages with individual feeders and had free access to feed and water. The daily feed consumption and the weekly body weight were recorded. No significant differences were found between treatments for body weight gain, feed intake and feed conversion.